The Influence of Company Fundamentals and Director Characteristic towards Fair Value Measurement in the Indonesian Banking Industry - Riska Delisa Haryono; Bernadia Linggar Yekti Nugraheni (Soegijapranata Catholic University, 2024)
Fair value is part of the International Financial Reporting Standards (IFRS) which attract attention of researchers due to its controversial issues. Studies investigating factors influencing opportunistic behaviour through fair value figures in developing countries are limited. This study aims to investigate the effect of company fundamental factors on fair value. This research applies multiple regression of banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. The fundamental factors, as independent variables are return on equity (ROE), ratio of operating expense on operating income (OEOI), capital adequacy ratio (CAR) and the proportion of female directors. Meanwhile, the dependent variable is fair value through modelling calculation i.e. fair value level 3 inputs. This study found that only OEOI significant influence fair value level 3 inputs. Meanwhile, ROE, CAR, and the proportion of females in the board of directors does not significant influence on fair value level 3 inputs. The study implications Indonesian banking industries should prioritize fair value disclosure, especially at level 3, as it provides crucial information about a company's performance and condition, potentially enabling investors to evaluate its performance.